Control of a specific motor program by a small brain area in zebrafish - Fajardo, Otto; Zhu, Peixin; Friedrich, Rainer W. (Frontiers in Neural Circuits, 2013)
Complex motor behaviors are thought to be coordinated by networks of brain nuclei that may control different elementary motor programs. Transparent zebrafish larvae offer the opportunity to analyze the functional organization of motor control networks by optical manipulations of neuronal activity during behavior. We examined motor behavior in transgenic larvae expressing channelrhodopsin-2 throughout many neurons in the brain. Wide-field optical stimulation triggered backward and rotating movements caused by the repeated execution of J-turns, a specific motor program that normally occurs during prey capture. Although optically evoked activity was widespread, behavioral responses were highly coordinated and lateralized. 3-D mapping of behavioral responses to local optical stimuli revealed that J-turns can be triggered specifically in the anterior-ventral optic tectum and/or the adjacent pretectum. These results suggest that the execution of J-turns is controlled by a small group of neurons in the midbrain that may act as a command center. The identification of a brain area controlling a defined motor program involved in prey capture is a step towards a comprehensive analysis of neuronal circuits mediating sensorimotor behaviors of zebrafish.